2022
DOI: 10.1002/eap.2570
|View full text |Cite
|
Sign up to set email alerts
|

Contrasting responses of native and introduced mammal communities to fire mosaics in a modified landscape

Abstract: Planned fire is increasingly recognized as an important tool in conservation, but other factors such as land‐use change may hinder the ability of land managers to use fire for the benefit of biodiversity. The mosaic of past fires in native vegetation may interact with the mosaic of other land‐cover types in human‐modified landscapes, yet the effects of these interactions on mammal communities are unknown. We investigated the responses of ground‐dwelling mammal community composition and species richness to inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 88 publications
(106 reference statements)
0
2
0
Order By: Relevance
“…This can be due to reduced opportunities for dispersal and colonisation (McAlpin, 2001;Lazzari, 2019) and loss of vegetation cover which is ideal for survival of this species (Ridley et al, 2020;Ridley and Schlesinger, 2023). On the other hand, properly prescribed burning can be a driver of species richness and community composition on natural ecosystems (Cadenhead et al, 2016;Rainsford et al, 2021;Zylinski and Swan, 2022). Our study demonstrated that time since the last fire had an influence on dietary diversity though it was not statistically significant (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…This can be due to reduced opportunities for dispersal and colonisation (McAlpin, 2001;Lazzari, 2019) and loss of vegetation cover which is ideal for survival of this species (Ridley et al, 2020;Ridley and Schlesinger, 2023). On the other hand, properly prescribed burning can be a driver of species richness and community composition on natural ecosystems (Cadenhead et al, 2016;Rainsford et al, 2021;Zylinski and Swan, 2022). Our study demonstrated that time since the last fire had an influence on dietary diversity though it was not statistically significant (Figure 3).…”
Section: Discussionmentioning
confidence: 68%
“…This may indicate that there is a greater variety of food items in recently burned areas, or that skinks are switching to new items in those areas if preferred resources are less available. Fire ecology studies in other animals have shown similar increases in animal diversity in recently burned areas (Zylinski and Swan, 2022). Notably, though from limited sample sizes, diet diversity in fire scars of 2008 and 2012 were lower than that in the 2002 fire scar.…”
Section: Discussionmentioning
confidence: 79%